Cultural Approaches to the History of Medicine
XXIII, 241 p.
Keywords: A pioneering contribution to the cultural history of medicine exploring issues as diverse as dissection of the heart, childbirth, masturbation, animal care, hermaphrodites, orthopaedics, 'miracle' drugs, smallpox and sex advice in different European cultures from the 1600s to the present day. Each case study illustrates various roles of mediation; reconciling conflicting ideas in the medical encounter; as an instrument of domination, or conversely, of resistance. Roy Porter's brilliant foreword conveys the methodological significance as well as the pleasure of these essays.